1996
DOI: 10.1007/bf02252932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic sciatic nerve lesion on the neurogenic inflammatory response in intact and acutely injured denervated rat skin

Abstract: A supersensitivity to the neuropeptide substance P (SP) has been shown to develop in post-terminal membranes of many denervated tissues. This study examined changes in the sensitivity of post-terminal vascular receptors to SP and calcitonin gene-related peptide (CGRP) in rat skin microvasculature following sciatic nerve section. In anaesthetised rats, 0.5 cm of sciatic nerve in the right mid-thigh region was removed. Two weeks later, SP (100 microM) and sodium nitroprusside (SNP, 1 mM), a direct smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Alternatively, other factors (e. g. endogenous opioids) could have contributed to the reduction in the vascular response to BK as they are known to inhibit sensory nerve activity [26]. It has been suggested that the opioid system is activated during blister induction in rats with chronic nerve injury [27]. Our current results suggest that the B 2 receptor is the major receptor involved in regulating BK-induced vasodilatation under this experimental condition.…”
Section: Discussionsupporting
confidence: 50%
“…Alternatively, other factors (e. g. endogenous opioids) could have contributed to the reduction in the vascular response to BK as they are known to inhibit sensory nerve activity [26]. It has been suggested that the opioid system is activated during blister induction in rats with chronic nerve injury [27]. Our current results suggest that the B 2 receptor is the major receptor involved in regulating BK-induced vasodilatation under this experimental condition.…”
Section: Discussionsupporting
confidence: 50%
“…It has previously been shown that CCI rats, and rats with sciatic nerve lesions, exhibit enhanced xanthine oxidase in sciatic nerve 47 and reduced vasodilatory responses to either the neuropeptides substance P and CGRP or the nitric oxide donor sodium nitroprusside applied at the base of a skin blister on the foot pad 2,3,47 . These findings indicate that nerve injury can induce endoneurial oxidative stress and diminished vascular reactivity in hind paw skin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent parallel studies by other groups suggest that microvascular dysfunction and the resulting production of reactive oxygen and nitrogen species may contribute to neuropathic pain (including chronic constriction injury (CCI) of the sciatic nerve 2,3,31 , painful diabetic neuropathy (PDN) 21,24,42,45,48,74 and chemotherapy-induced painful neuropathy (CIPN) 20,22,49,50 . Therefore, it is expected that treatments aimed at enhancing tissue oxygenation by reducing arterial vasospasm and capillary slow-flow/no-reflow will also relieve allodynia in animal models of nerve constriction, PDN and CIPN.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the possibility that opioid receptors could be activated by endogenous hemorphins or endogenous opioids based on their availability, we examined the effect of hemorphin-7 on the vascular response to SP in a model where the involvement of opioids has previously been established, namely, a model of acute injury induced in a denervated skin site due to chronic nerve lesion [3]. The results showed that the vascular response to SP perfused over a denervated skin site is significantly reduced compared to the responses obtained in the acute injury model.…”
Section: Discussionmentioning
confidence: 99%
“…Using a blister model of inflammation, we have previously reported that the decrease in the peripheral inflammatory response in chronic inflammatory conditions e.g. chronic nerve injury conditions [3] can be partially reversed by the opioid antagonist naloxone. Our previous study therefore suggests that endogenous opioids are activated under chronic inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%